2011
DOI: 10.1093/carcin/bgr076
|View full text |Cite
|
Sign up to set email alerts
|

Distinct contributions of angiogenesis and vascular co-option during the initiation of primary microtumors and micrometastases

Abstract: Primary tumors and metastases have been thought to initiate avascularly as multicellular aggregates and later induce angiogenesis or initiate vascularly by co-opting pre-existing host blood vessels without inducing angiogenesis. These two distinct concepts of microtumor vascularization have raised significant controversies. To clarify intratumoral vascularization and tumor cell behaviors at single-cell level during the earliest stage of microtumor initiation, we established primary and metastatic microtumor mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 36 publications
4
56
0
Order By: Relevance
“…However, the association between angiogenesis and lncRNAs in CRC are still not reported yet. Recently, more evidences indicated that angiogenesis may not be necessary for carcinoma metastases [158, 159], whereas co-opting host vessels is the essential choice for tumor cells survive [160]. Surprisingly, vessel co-option may respond for approximately 40% metastases in mCRC [161].…”
Section: Discussionmentioning
confidence: 99%
“…However, the association between angiogenesis and lncRNAs in CRC are still not reported yet. Recently, more evidences indicated that angiogenesis may not be necessary for carcinoma metastases [158, 159], whereas co-opting host vessels is the essential choice for tumor cells survive [160]. Surprisingly, vessel co-option may respond for approximately 40% metastases in mCRC [161].…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is supported by results from injections of melanoma cells of different malignancy into flk1::egfp-transgenic zebrafish embryos. 100-300 non-metastatic B16 mouse melanoma cells were necessary to induce angiogenesis, whereas the metastatic melanoma cell line B16-F10 required only 15-30 cells to induce an angiogenic response (Zhao et al, 2011). The angiogenesis-inducing capacity of melanoma cells thus seems to depend on their ability to initiate and maintain a pro-angiogenic signaling threshold.…”
Section: Discussionmentioning
confidence: 99%
“…According to the results of Zhao and co-workers [95], co-option is a strategy providing survive of tumor in difficult conditions. This process is only seemingly more favourable than sprouting angiogenesis.…”
Section: Mechanisms Of Tumor Angiogenesismentioning
confidence: 99%
“…From the results on Danio rerio, it was found that when tumor is composed of about 20-30 cells, a co-option is observed, without angiogenesis induction. However, when the amount of tumor cells is 200-300, almost immediately sprouting angiogenesis begins [95].…”
Section: Mechanisms Of Tumor Angiogenesismentioning
confidence: 99%